Adjusting the Sails: Québec–U.S. Commerce Under the Trump Administration. (December 2017) - Lachapelle, Guy; Masson, Tristan
Abstract : With the arrival of the Trump administration, the continental economy has come under the spotlight. Starting with an overview of commerce between Québec and the U.S., and the premise that the two have a common interest in an uninterrupted trade relationship, this article seeks to investigate Québec's policies and paradiplomacy in wake of this atypical policy change. In the policy dimension, we trace the historical trajectory of bilateral relations, the policymaking process, including the role of Canadian federalism, and analyze key components of the province's most recent international policy as well as Canada's new foreign policy vision. In the paradiplomacy dimension, we take stock of the province's diplomatic toolkit by assessing its deployment on the ground, the political channels at its disposal and the rising importance of digital diplomacy.